2015
DOI: 10.5152/akd.2014.5418
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cytochrome P450 2C19 polymorphism on the occurrence of one-year in-stent restenosis in patients who underwent percutaneous coronary intervention: A case-match study

Abstract: ObjectiveIn this case-match study, we evaluated the impact of the CYP2C19*2 polymorphism in the occurrence of in-stent restenosis during a 1-year follow-up period despite adequate dual anti-platelet therapy in Iranian patients having undergone percutaneous coronary intervention (PCI).MethodsThis study, conducted at a tertiary referral heart center in Tehran, recruited 100 patients: 50 patients had in-stent restenosis after PCI during a 1-year follow-up and were compared to another 50 patients without in-stent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…The findings from this study show that despite a higher proportion of CYP2C19*2 allele carriers exhibiting coronary ISR within 1 year compared to non-carriers, and *2 allele carriers being 4.08-times more likely to exhibit ISR than non-carriers, the association between CYP2C19*2 allele carrier status and development of coronary ISR was not statistically significant (p > 0.05). Our findings are similar to Nozari et al 25 who reported that the prevalence of ISR after PCI was higher in *2 allele carriers but without a statistically significant relationship, and contrast to Ruedlinger et al, 26 who identified non-carriers of the *2 allele with higher incidence of coronary ISR.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings from this study show that despite a higher proportion of CYP2C19*2 allele carriers exhibiting coronary ISR within 1 year compared to non-carriers, and *2 allele carriers being 4.08-times more likely to exhibit ISR than non-carriers, the association between CYP2C19*2 allele carrier status and development of coronary ISR was not statistically significant (p > 0.05). Our findings are similar to Nozari et al 25 who reported that the prevalence of ISR after PCI was higher in *2 allele carriers but without a statistically significant relationship, and contrast to Ruedlinger et al, 26 who identified non-carriers of the *2 allele with higher incidence of coronary ISR.…”
Section: Discussionsupporting
confidence: 90%
“…The Fisher's exact p-value obtained in our study (0.067) exceeds the 0.05 level of significance by only a small margin, despite the very small sample size (29 patients with ISR). Compared to our study, Nozari et al 25 had a larger sample of patients with ISR (50 patients) and a higher p-value (0.273) was obtained. Hence, given the small sample size, the findings from our study should not be ignored.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Nozari et al (21) in a case-match study assessed the role of CYP2C19*2 polymorphism in the occurrence of in-stent restenosis during a 1-year follow-up period in Iranian patients who underwent PCI. The results of this study showed no significant association with in-stent restenosis one year after PCI in patients with CYP2C19*1*2 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent manuscript, published in this issue Nozari et al ( 1 ) entitled “The impact of cytochrome P450 2C19 polymorphism on the occurrence of one-year in-stent restenosis in patients who underwent percutaneous coronary intervention: A case-match study.” evaluated the impact of cytochrome P450 2 (CYP2C19*2) polymorphism in the occurrence of in-stent restenosis among Iranian patient population.…”
mentioning
confidence: 99%